Exclusive breastfeeding, complementary feeding and association with body fat excess among schoolchildren in Florianópolis, Santa Catarina, Brazil - Priscila Schramm Gonsalez; Anabelle Retondario; Liliana Paula Bricarello; David Alejandro González-Chica; Diego Augusto Santos Silva; Francisco de Assis Guedes de Vasconcelos
Abstract Objectives: to analyze the association between exclusive breastfeeding duration (EBF) and the age at which complementary feeding was introduced (CF) with the excess of body fat (BF) in schoolchildren from Florianópolis/SC, southern of Brazil. Methods: cross sectional study, with probability sample of 1,531 schoolchildren aged 7-10 years from Florianópolis/SC. The percentage of BF was defined based on triceps and subscapular skinfolds. Information about EBF, CF and confounders variables were obtained through a questionnaire sent to parents or guardians. Multivariate analyzes were performed using Poisson. Results: the prevalence of BF excess was 37.9% (CI95%: 32.4; 43.6), and 30.6% of children received EBF for 4-6 months (CI95%: 17, 3; 48, 2). The duration of EBF less than 4 or more than 6 months was associated with higher prevalence of BF excess, even after adjustment (p=0.015). Introduction of food groups had no association with BF excess. Conclusions: the association between EBF and the excess of body fat for less than 4 months and higher prevalence of BF excess is probably a consequence of early introduction of others milk types, whilst association between EBF for more than 6 months and higher prevalence of BF excess is because of a catch-up growth situation.